PREDIKCIJA REALIZACIJE PROGRAMSKIH ZADATAKA IZ SPORTSKIH IGARA NA OSNOVU BAZIČNO-MOTORIČKIH SPOSOBNOSTI UČENIKA - Vildane Jashari; Abedin Ibrahimi; Fahrudin Aščić; Zlatko Topić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2011)
In this study comprised a sample of subjects students sixth grade two elementaryschools in Kalesija-Tuzla. We studied the properties that are considered fundamental anthropologicaldimensions relevant for the implementation of the curriculum as the level and impact of the anthropological dimension of the grade Physical and health education. Selection of variables was based on previous experiences and research similarissues. Selection of variables of motor abilities was carried out based on the criteria of metriccharacteristics which limit is 0.80 or more and makes them 12 variables. To study the motor space were applied tests that reflect the latent dimensions of thechoice of mechanisms for structuring movements, synergistic mechanisms of automaticity and tonus regulation, then the mechanisms for regulation of excitation. Property criterion variables are subpremises three sports games-volleyball, basketball and football. These tests are considered a wide range of tests, that are representative of concerted action function of multiple organs and organ systems.